Java Programming Essentials - Roberts, Simon (Pearson IT Certification, 2021)
8+ Hours of Video Instruction Overview Build a solid understanding of core features of the Java programming language. This course brings you the skills and knowledge needed to understand the essentials of the Java language. In this more than 8 hour video course, you will develop a depth of understanding significantly beyond what's typical for programmers who learn a language on the job. The key knowledge learned in this course will help you increase your skills, ace an interview, and give you the core knowledge you need to truly understand Java. This course will also help you with the Java 11 certification exam. This course focuses on basic structures, packages, command-line operations, operators and expressions, language control structures, iteration structures, essentials of class and object creation, and garbage collection. About the Instructor Simon Roberts wrote his first program in 1978 and was a programmer writing in a variety of assembly and high-level languages for a dozen years before he joined Sun Microsystems in 1995 to 2004. While at Sun he created training courses on a diverse range of Java topics and developed the original Sun Certified Java Programmer and Developer exams. Since leaving Sun in 2004, he spends most of his time helping people improve their skills in Java, Scala, Python, and JavaScript, offering training in classroom, recorded video, and live web-based formats. You can follow Simon Roberts here: https://www.linkedin.com/in/simonhgroberts/ Skill Level: Beginner to Intermediate Learn How To: Structure a Java source file Declare and use packages Build and execute your code from the command-line Use operators and expressions Use conditional and loop structures Declare simple classes and instantiate objects Understand garbage collection Who Should Take This Course: Programmers and IT professionals wishing to transition to the Java Programming Language. Anyone wanting to learn the Java Programming Language in more detail, for example for an interview or examination, whether academic or professional. Course Requirements: A working knowledge of programming, not necessarily in the Java language About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: A ...